Peer Instruction as a Transformative Approach for Enhanced Academic Performance in General Physics 1 - Bayona, Darryl (Journal of Interdisciplinary Perspectives, 2024)
The widespread reliance on traditional teaching methods in science education has been identified as a contributing factor to the below-standard performance of Filipino learners in both national and international assessments. This underscores the need to integrate active learning strategies into pedagogical practices. This study aimed to examine the effectiveness of peer instruction in enhancing the academic performance of Grade 12 learners in General Physics 1 during the third quarter of the school year 2023–2024. A total of 80 learners from the General Academic Strand at Gen. Tiburcio De Leon National High School in Valenzuela City participated in the study. They were equally divided (n = 40) into an experimental group, where the peer instruction approach was implemented, and a control group, where the traditional teaching method was employed. The intervention lasted three weeks and was framed within a quasi-experimental research design, utilizing a pre-test and post-test structure. The assessment tool used was expert-validated and reliability-tested. Data analysis was conducted using independent and dependent sample t-tests with IBM SPSS software, adhering to a significance threshold of p < 0.05. The results revealed a statistically significant improvement in academic performance within the experimental group compared to the control group, indicating that peer instruction is a more effective instructional strategy than traditional methods. The study recommends incorporating peer instruction into teaching practices, supported by comprehensive teacher upskilling programs, to foster an active learning environment.